Chan before chan meditation, repentance, and visionary experience in Chinese Buddhism - Greene, Eric Matthew (Studies in East Asian Buddhism, 2021)
What is Buddhist meditation? What is going on-and what should be going on-behind the closed or lowered eyelids of the Buddha or Buddhist adept seated in meditation? And in what ways and to what ends have the answers to these questions mattered for Buddhists themselves? Focusing on early medieval China, this book takes up these questions through a cultural history of the earliest traditions of Buddhist meditation (chan), before the rise of the Chan (Zen) School in the eighth century. In sharp contrast to what would become typical in the later Chan School, early Chinese Buddhists approached the ancient Buddhist practice of meditation primarily as a way of gaining access to a world of enigmatic but potentially meaningful visionary experiences. In Chan Before Chan, Eric Greene brings this approach to meditation to life with a focus on how medieval Chinese Buddhists interpreted their own and others' visionary experiences and the nature of the authority they ascribed to them.